Reproductive Traits and Population Characteristics of Atule mate (Cuvier, 1833) From the Gulf of Mannar: Implications for Minimum Legal Size - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; K. Karuppasamy; Percy Paulin J; S. Pearlin Arul Granap; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Competition influences tree growth, but not mortality, across environmental gradients in Amazonia and tropical Africa - Danaë M. A. Rozendaal; Oliver L. Phillips; Simon L. Lewis; Kofi Affum‐Baffoe; Esteban Alvarez-Davila; Ana Andrade; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Timothy R. Baker; Olaf Bánki; Roel J. W. Brienen; José Luis C. Camargo; et al. (Ecology, 2020)
Competition among trees is an important driver of community structure and dynamics in tropical forests. Neighboring trees may impact an individual tree’s growth rate and probability of mortality, but large‐scale geographic and environmental variation in these competitive effects has yet to be evaluated across the tropical forest biome. We quantified effects of competition on tree‐level basal area growth and mortality for trees ≥10‐cm diameter across 151 ~1‐ha plots in mature tropical forests in Amazonia and tropical Africa by developing nonlinear models that accounted for wood density, tree size, and neighborhood crowding. Using these models, we assessed how water availability (i.e., climatic water deficit) and soil fertility influenced the predicted plot‐level strength of competition (i.e., the extent to which growth is reduced, or mortality is increased, by competition across all individual trees). On both continents, tree basal area growth decreased with wood density and increased with tree size. Growth decreased with neighborhood crowding, which suggests that competition is important. Tree mortality decreased with wood density and generally increased with tree size, but was apparently unaffected by neighborhood crowding. Across plots, variation in the plot‐level strength of competition was most strongly related to plot basal area (i.e., the sum of the basal area of all trees in a plot), with greater reductions in growth occurring in forests with high basal area, but in Amazonia, the strength of competition also varied with plot‐level wood density. In Amazonia, the strength of competition increased with water availability because of the greater basal area of wetter forests, but was only weakly related to soil fertility. In Africa, competition was weakly related to soil fertility and invariant across the shorter water availability gradient. Overall, our results suggest that competition influences the structure and dynamics of tropical forests primarily through effects on individual tree growth rather than mortality and that the strength of competition largely depends on environment‐mediated variation in basal area.

Retraction Note: Aluminum in Neurological and Neurodegenerative Disease - Donald R. C. McLachlan; Catherine Bergeron; Peter N. Alexandrov; William J. Walsh; Aileen I. Pogue; Maire E. Percy; Theodore P. A. Kruck; Zhide Fang; Nathan M. Sharfman; Vivian Jaber; Yuhai Zhao; Wenhong Li; et al. (Molecular Neurobiology, 2020)

Species Matter: Wood Density Influences Tropical Forest Biomass at Multiple Scales - Oliver L. Phillips; Martin J. P. Sullivan; Tim R. Baker; Abel Monteagudo Mendoza; Percy Núñez Vargas; Rodolfo Vásquez (Surveys in Geophysics, 2019)

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

RETRACTED ARTICLE: Aluminum in Neurological and Neurodegenerative Disease - Donald R. C. McLachlan; Catherine Bergeron; Peter N. Alexandrov; William J. Walsh; Aileen I. Pogue; Maire E. Percy; Theodore P. A. Kruck; Zhide Fang; Nathan M. Sharfman; Vivian Jaber; Yuhai Zhao; Wenhong Li; et al. (Molecular Neurobiology, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Predicting trait‐environment relationships for venation networks along an Andes‐Amazon elevation gradient - Benjamin Blonder; Norma Salinas; Lisa Patrick Bentley; Alexander Shenkin; Percy O. Chambi Porroa; Yolvi Valdez Tejeira; Cyrille Violle; Nikolaos M. Fyllas; Gregory R. Goldsmith; Roberta E. Martin; Gregory P. Asner; Sandra Díaz; et al. (Ecology, 2017)
Understanding functional trait‐environment relationships ( TER s) may improve predictions of community assembly. However, many empirical TER s have been weak or lacking conceptual foundation. TER s based on leaf venation networks may better link individuals and communities via hydraulic constraints. We report measurements of vein density, vein radius, and leaf thickness for more than 100 dominant species occurring in ten forest communities spanning a 3,300 m Andes‐Amazon elevation gradient in Peru. We use these data to measure the strength of TER s at community scale and to determine whether observed TER s are similar to those predicted by physiological theory. We found strong support for TER s between all traits and temperature, as well weaker support for a predicted TER between maximum abundance‐weighted leaf transpiration rate and maximum potential evapotranspiration. These results provide one approach for developing a more mechanistic trait‐based community assembly theory.

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Understanding the spectacular failure of DNA barcoding in willows ( Salix ): Does this result from a trans‐specific selective sweep? - Diana M. Percy; George W. Argus; Quentin C. Cronk; Aron J. Fazekas; Prasad R. Kesanakurti; Kevin S. Burgess; Brian C. Husband; Steven G. Newmaster; Spencer C.H. Barrett; Sean W. Graham (Molecular Ecology, 2014)
Willows ( Salix : Salicaceae) form a major ecological component of Holarctic floras and consequently are an obvious target for a DNA ‐based identification system. We surveyed two to seven plastid genome regions (~3.8 kb; ~3% of the genome) from 71 Salix species across all five subgenera, to assess their performance as DNA barcode markers. Although Salix has a relatively high level of interspecific hybridization, this may not sufficiently explain the near complete failure of barcoding that we observed: only one species had a unique barcode. We recovered 39 unique haplotypes, from more than 500 specimens, that could be partitioned into six major haplotype groups. A unique variant of group I (haplotype 1*) was shared by 53 species in three of five Salix subgenera. This unusual pattern of haplotype sharing across infrageneric taxa is suggestive of either a massive nonrandom coalescence failure (incomplete lineage sorting), or of repeated plastid capture events, possibly including a historical selective sweep of haplotype 1* across taxonomic sections. The former is unlikely as molecular dating indicates that haplotype 1* originated recently and is nested in the oldest major haplotype group in the genus. Further, we detected significant non‐neutrality in the frequency spectrum of mutations in group I, but not outside group I, and demonstrated a striking absence of geographical (isolation by distance) effects in the haplotype distributions of this group. The most likely explanation for the patterns we observed involves recent repeated plastid capture events, aided by widespread hybridization and long‐range seed dispersal, but primarily propelled by one or more trans‐species selective sweeps.

Germplasm evaluation and transfer of Verticillium wilt resistance from Pima (Gossypium barbadense) to Upland cotton (G. hirsutum) - Jinfa Zhang; S. Sanogo; R. Flynn; Jit B. Baral; S. Bajaj; S. E. Hughs; Richard G. Percy (Euphytica, 2012)

Application of a single-objective, hybrid genetic algorithm approach to pharmacokinetic model building - Eric A. Sherer; Mark E. Sale; Bruce G. Pollock; Chandra P. Belani; Merrill J. Egorin; Percy S. Ivy; Jeffrey A. Lieberman; Stephen B. Manuck; Stephen R. Marder; Matthew F. Muldoon; Howard I. Scher; David B. Solit; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Increasing Underrepresented Scientists in Cancer Research: The UCSD CURE Program - Lawrence Alfred; Paula R. Beerman; Zunera Tahir; Sheila F. LaHousse; Percy Russell; Georgia Robins Sadler (Journal of Cancer Education, 2011)

Spatial patterns of plant diversity below‐ground as revealed by DNA barcoding - PRASAD R. KESANAKURTI; ARON J. FAZEKAS; KEVIN S. BURGESS; DIANA M. PERCY; STEVEN G. NEWMASTER; SEAN W. GRAHAM; SPENCER C. H. BARRETT; MEHRDAD HAJIBABAEI; BRIAN C. HUSBAND (Molecular Ecology, 2011)
Our understanding of the spatial organization of root diversity in plant communities and of the mechanisms of community assembly has been limited by our ability to identify plants based on root tissue, especially in diverse communities. Here, we test the effectiveness of the plastid gene rbcL , a core plant DNA barcoding marker, for investigating spatial patterns of root diversity, and relate observed patterns to above‐ground community structure. We collected 3800 root fragments from four randomly positioned, 1‐m‐deep soil profiles (two vertical transects per plot), located in an old‐field community in southern Ontario, Canada, and extracted and sequenced DNA from 1531 subsampled fragments. We identified species by comparing sequences with a DNA barcode reference library developed previously for the local flora. Nearly 85% of sampled root fragments were successfully sequenced and identified as belonging to 29 plant species or species groups. Root abundance and species richness varied in horizontal space and were negatively correlated with soil depth. The relative abundance of taxa below‐ground was correlated with their frequency above‐ground ( r = 0.73, P = 0.0001), but several species detected in root tissue were not observed in above‐ground quadrats. Multivariate analyses indicated that diversity was highly structured below‐ground, and associated with depth, root morphology, soil chemistry and soil texture, whereas little structure was evident above‐ground. Furthermore, analyses of species co‐occurrence indicates strong species segregation overall but random co‐occurrence among confamilials. Our results provide insights into the role of environmental filtering and competitive interactions in the organization of plant diversity below‐ground, and also demonstrate the utility of barcoding for the identification of plant roots.

Status of the USA cotton germplasm collection and crop vulnerability - T. P. Wallace; D. Bowman; B. T. Campbell; P. Chee; O. A. Gutierrez; R. J. Kohel; J. McCarty; G. Myers; R. Percy; F. Robinson; W. Smith; D. M. Stelly; et al. (Genetic Resources and Crop Evolution, 2009)

Promoter anchored amplified polymorphism based on random amplified polymorphic DNA (PAAP-RAPD) in cotton - Mingxiong Pang; R. G. Percy; Ed. Hughs; Jinfa Zhang (Euphytica, 2009)

Murine CD146 is widely expressed on endothelial cells and is recognized by the monoclonal antibody ME-9F1 - Arnhild Schrage; Christoph Loddenkemper; Ulrike Erben; Uta Lauer; Gert Hausdorf; Peter R. Jungblut; Judith Johnson; Percy A. Knolle; Martin Zeitz; Alf Hamann; Katja Klugewitz (Histochemistry and Cell Biology, 2008)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

Strategies, Effectiveness and Rationale of Vector-borne Disease Control in the Pastoralist System of South-western Uganda - A Mugisha; A. McLeod; R. Percy; E. Kyewalabye (Tropical Animal Health and Production, 2005)

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Interacting elevated CO 2 and tropospheric O 3 predisposes aspen ( Populus tremuloides Michx.) to infection by rust ( Melampsora medusae f. sp. tremuloidae ) - D. F. Karnosky; Kevin E. Percy; Bixia Xiang; Brenda Callan; Asko Noormets; Blanka Mankovska; Anthony Hopkin; Jaak Sober; Wendy Jones; R. E. Dickson; J. G. Isebrands (Global Change Biology, 2002)
We investigated the interaction of elevated CO 2 and/or (Ozone) O 3 on the occurrence and severity of aspen leaf rust ( Melampsora medusae Thuem. f. sp. tremuloidae ) on trembling aspen ( Populus tremuloides Michx.). Furthermore, we examined the role of changes in leaf surface properties induced by elevated CO 2 and/or O 3 in this host–pathogen interaction. Three‐ to five‐fold increases in levels of rust infection index were found in 2 consecutive years following growing‐season‐long exposures with either O 3 alone or CO 2 + O 3 depending on aspen clone. Examination of leaf surface properties (wax appearance, wax amount, wax chemical composition, leaf surface and wettability) suggested significant effects by O 3 and CO 2 + O 3 . We conclude that elevated O 3 is altering aspen leaf surfaces in such a way that it is likely predisposing the plants to increased infection by aspen leaf rust.

State of Science and Knowledge Gaps with Respect to Air Pollution Impacts on Forests: Reports from Concurrent IUFRO 7.04.00 Working Party Sessions - K. Percy; J. Bucher; J. Cape; M. Ferretti; R. Heath; H.E. Jones; D. Karnosky; R. Matyssek; G. Muller-Starck; E. Paoletti; U. Rosengren-Brinck; L. Sheppard; et al. (Water, Air, & Soil Pollution, 1999)

Sexual conflict over fertilizations: female bluethroats escape male paternity guards - Arild Johnsen; Jan T. Lifjeld; Percy A. Rohde; Craig R. Primmer; Hans Ellegren (Behavioral Ecology and Sociobiology, 1998)

Toward a theory of biological‐physical control of harmful algal bloom dynamics and impacts - Percy L. Donaghay; Thomas R. Osborn (Limnology and Oceanography, 1997)
A growing body of laboratory, field, and theoretical work suggests that the dynamics of harmful algal blooms and their impacts on other organisms are frequently controlled not only by physiological responses to local environmental conditions as modified by trophic interactions, but also by a series of interactions between biological and physical processes occurring over an extremely broad range of temporal and spatial scales. All too frequently, major gaps in our ability to identify, measure, and model the underlying biological and physical processes and their interactions over the appropriate temporal and spatial scales have prevented the quantitative assessment of the importance of these factors in causing past blooms and the development of predictive models of bloom dynamics and impacts. For these reasons, we have combined fluid continuity equations with a conservation equation for population dynamics to quantify how biological and physical processes and their interactions affect the population dynamics of harmful algae and their potential impact on other organisms. Applications of the resulting numerical and conceptual models to toxic algal blooms in upwelling systems and pycnocline layers suggest not only that bloom dynamics and impacts are sensitive to biological‐physical interactions occurring at multiple scales, but also that such interactions may be critical components of the life‐history strategies of these organisms.